A heuristic to minimise the idle time of the rental/critical machine in a flowshop. (2015) - Pugazhenthi, R.; Xavior, M. Anthony
This article deals with a special case of flowshop. In which some special purpose machines are taken for rent and engaged for processing some special orders. The operation cost is to be optimised by increasing the utilisation or by reducing the idle time of such rental machine to availability. Even though many researchers made attempts with this objective, this paper proposed a new heuristic to diminish the idle time of the rental/critical machine. The Taillard benchmark problems are solved to analyse the proposed heuristic statistically. The proposed heuristic outperformed with existing heuristics significantly and the results are tabulated and analysed. Hence, the proposed heuristic cut down the cost of the rental/critical machine significantly.